Desenvolvimento? como compreender e mensurar: um estudo sobre o município do Conde - Ba - SOUZA, José Gileá de (2016)
This thesis has as its purpose the development and It´s indicators. The problematics investigated and debated searched to answer the following question: How and in which ways can we measure the development of a territory? This is a complex problem due to Its polissemic nature of development and Its several forms of measure. The objective of this research consists in evaluate the adequacy of the proper means of mensuration of development and subsidiary discuss the traditional approach and modern embrace of development; to analyse the forms of measure, evaluation and perception of development; and evaluate the level of development of a territory. As method, the thesis presents a critical review about the origins of the concept development and It´s several approaches, well as show the traditional methods of measure, ones that are based on economic dimension and by more modern methods that go further and embrace other dimensions. The methodology used in field by this thesis consists in use of both qualitative and quantitative embrace by using secondary data and administrative registry, treated statistically, and primary data collected by informal interviewing, chatting, semi-structure interview and by active observation. The analysis of the data and the results are presented in shape of spreadsheets, photographic registries and transcriptions of the perception of the population. For this was used a Case Study which aggregates as Its base an empiric study of a territory located on the north shore of the State of Bahia. The Município do Conde, that even being a place of occupation with an ancient history since the brazilian colonization, only experimented big changes in Its space, environment, economic and social structure in the 1970`s with the arrival of big reforestation companies in their territory and principally in the 1990`s when the highway Linha Verde was constructed. As result the usual forms of measure the development does not translate with accuracy all the reality of the territory for Its population. Also every result of development related to the county presents a lower degree of development and the perception of Its population indicates a reality even worst.